The Effectiveness of Virtual Class With Zoom Meetingin Teaching Evaluation Lectures Indonesian - Helda, Trisna; Kemal, Edwar; Pebriani, Yulia; Marni, Silvia (Language Pedagogy Study Program, Faculty of Languages and Arts, Universitas Negeri Padang, Indonesia, 2022)
Covid-19 forced changes in the lecture process. Online learning is the main solution taken, so that learning continues to run well. All students conduct their lectures online, from their respective places of residence, due to Covid-19. Without being discouraged, the lecturers and students remained enthusiastic in carrying out the lectures. Virtual classth rough various applications, one of which is zoom meeting. The application of zoom meetingis still very common for students because usually lecturers teach directly face to face. The purpose of this article is to find out the effectiveness of implementing virtual class with zoom meetingin evaluating Indonesian language teaching evaluation lectures. The research data was taken using a quantitative method, namely filling out a questionnaire using the Google form and distributing it to students who were selected as research samples for the Indonesian language and literature education study program at PGRI West Sumatra University who were taking an evaluation course for teaching Indonesian in the odd semester of 2021/ In 2022 there will be 34 students. From the survey results, the research results show that zoom meetings are less effective in evaluating Indonesian language teaching lectures, however, they are already effective in virtual classlearning and can be used as online learning applications. So it can be concluded that students can still continue lectures in a virtual classor indirectly by using a zoom meetingin the Indonesian language teaching evaluation lecture process.